Tahapan-Tahapan Transaksi Bisnis dan Dokumen Bisnis - Ida Nuraida (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
Every business deals with forms in their daily operational activities. We should know how to design and fill out business document forms as a lot of companies have their own form designs according to their companies' needs and situations. In administrative office management, knowledge of how to design and fill out business documents is very important for us in the real working environment. Learning the basics of business documents also need our knowledge of accounting practice. The basic reason for the existence of business documents is that they are evident in some stages of business transactions. An example of business document application is described in PT Indrajaya Bandung, a company which produces many kinds of spring beds. The company has certain suppliers to fulfill their raw materials, and certain retailers to distribute their product to the end user. Both of them have a credit transaction with PT Indrajaya. By comparing between the theory of creating and using business document forms with the application of business documents, as stated in the example of PT lndrajaya, we can analyze and conclude the effectiveness and the efficiency of forms that they use for their business transactions.